Issues related to the quality of secondary education: the Case of Dire Dawa, Ethiopia - Belay Sitotaw Goshu; Melaku Masresha Woldeamanueal; Muhammad Ridwan (Budapest International Research and Critics University, 2024)
This study aimed to examine concerns regarding the quality of education in secondary schools in Dire Dawa City. It reflects the views of teachers and educational administrators on educational quality, issues, and recommendations for improving quality. A descriptive survey was conducted for this purpose. In this study, 235 city teachers were randomly selected. Despite access improvements, data shows slow progress in improving quality education in Ethiopia. Government officials, teachers, parents, teachers, students, and others expressed concern about the quality of education in general education schools in Dire Dawa City. The results revealed that schools should also provide an educational environment suitable for teaching and learning activities. In-service training or professional development is one of the key factors in quality education. However, the result revealed that 43% of the survey respondents had not attended in-service training in the past two years. Furthermore, 91.9 percent of the respondents believed cheating was a crucial problem for quality education. The local government should work with the university to address most of the issues raised in this study.